A análise de propostas pedagógicas em portais educacionais para docentes de Língua Inglesa: implicações para o ensino e a aprendizagem de línguas no contexto digital - Oliveira, Flávia Medianeira de (2009)
The enhancement of information and communication technologies has produced the development of new discursive genres (MARCUSCHI, 2002; HUCKIN, 2007), called digital genres, such as: e-mail, MSN, chats, forums, blogs, video conference, fotoblogs, videoblogs and orkut. Educational portals are one of these genres, which aim at displaying subjects and pedagogical activities in several fields (Mathematics, Chemistry, Physics, Arts, English, for example). Based on the studies of Genre Analysis and English Teaching and Learning, we analyzed English-educational portals aiming at: 1) investigating the genre function, 2) identifying the web owners and users role and 3) examining the rhetorical organization of subjects and pedagogical activities. Furthermore, in this research, we investigated the reading pedagogical activities displayed in the portals, with the objective of identifying the underlying teaching and learning principles and the teachers and learners role. In this context of investigation, we selected 15 free-access educational portals which have a focus on reading pedagogical activities and English teachers as target public. The results revealed that the portals present five rhetorical moves and eight optional moves in order to display subjects, pedagogical activities and methodological suggestions related to the English Teaching and Learning. The portals also work as interactive spaces to teachers exchange information and experiences with the others about the pedagogical practice. This investigation points out that portals reproduce and disseminate instructional materials produced in printed medium, with reading pedagogical activities based on behaviorist and communicational perspectives. In this sense, we concluded that the English-educational portals do not constitute a discursive space which can contribute to the development of critical pedagogy.